How do the Special Autonomy Fund, Village Fund, and Zakat interact in reducing poverty in Aceh Province? - Ridmailis, Ridmailis; Vivi, Vivi Silvia; Chenny, Chenny Seftarita (Technium Social Sciences Journal, 2024)
This study explores the interaction between Special Autonomy Fund, Village Fund, and Zakat in poverty reduction efforts in Aceh Province. As a region with special autonomy status, Aceh receives a transfer allocation from the central government, which aims to accelerate development and improve people's welfare. In addition, village funds managed directly by the village government and zakat collected through religious institutions play an important role in supporting the local economy and social of the poor. The purpose of this study is to analyze the effect of special autonomy fund, village fund, and zakat on poverty rate in Aceh Province in the short run and long run. The method used is Panel ARDL by analyzing data from 23 districts/cities in Aceh Province during the period 2015-2022. The estimation results show that the special autonomy fund variable has a negative and significant effect on the poverty rate in Aceh Province in the short term, but has no significant effect in the long term. The village fund variable has a negative and significant effect on poverty in the short term, but has a positive and significant effect in the long term. Zakat has a negative and significant effect on poverty both in the short and long term. The Aceh Provincial Government should conduct more intensive policies in reducing poverty, especially the variables of special autonomy funds, village funds and zakat so that these problems can be resolved.